ANALISIS TANTANGAN DAN INOVASI PEMBELAJARAN FIKIH DI MI TAHFIDZ ANNUR GENAHARJO DALAM IMPLEMENTASI KURIKULUM MERDEKA - Ngainin, Nurul; Ziana Dhurrotul Ainiyah; Achmad Fastabikhul A’mal (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to analyze the challenges and innovations in Fiqh learning at MI Tahfidz Annur Genaharjo within the framework of implementing the Merdeka Curriculum. This curriculum emphasizes contextual, differentiated, and project-based learning. However, in its implementation, teachers face various obstacles such as limited digital literacy, minimal technical training, and lack of supporting facilities. This study uses a qualitative descriptive approach with data collection techniques through semi-structured interviews and analyzed using thematic analysis methods. The results of the study show that teachers have developed various innovations such as blended learning, utilization of digital media (Kahoot, YouTube, Canva), and the application of differentiated learning according to students' learning styles. Despite facing challenges, teachers are able to create adaptive and contextual Fiqh learning. This study emphasizes the importance of improving teacher competence and strengthening system support so that Fiqh learning is in accordance with the spirit of the Merdeka Curriculum